1980
DOI: 10.1111/j.1432-1033.1980.tb04602.x
|View full text |Cite
|
Sign up to set email alerts
|

Lipoprotein Lipase: Some Effects of Activator Proteins

Abstract: This paper considers how apolipoprotein CII from human plasma lipoproteins and T1 and T2 proteins from egg yolk lipoproteins stimulate the activity of lipoprotein lipase. These activator proteins stabilized the enzyme much more effectively than a thousandfold higher concentration of albumin did, indicating a direct interaction with the enzyme. The effects of the activators were seen also at 1 M NaC1. Thus, forces other than electrostatic are implicated. Centrifugation experiments showed that '251-labeled lipas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
43
0

Year Published

1984
1984
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(49 citation statements)
references
References 36 publications
6
43
0
Order By: Relevance
“…Thus, in addition to activation, apoC-II also stabilized LPL. This is in accord with results from previous studies (30). The stabilizing effect of apoC-II is usually not recognized with other substrate systems used for measurements of LPL activity.…”
Section: Itc Can Be Used To Study the Influence Of Added Regulators Osupporting
confidence: 82%
See 1 more Smart Citation
“…Thus, in addition to activation, apoC-II also stabilized LPL. This is in accord with results from previous studies (30). The stabilizing effect of apoC-II is usually not recognized with other substrate systems used for measurements of LPL activity.…”
Section: Itc Can Be Used To Study the Influence Of Added Regulators Osupporting
confidence: 82%
“…The stabilization of LPL by addition of apoC-II, as seen in the present study, is usually not detected in other substrate systems. Therefore the magnitude of the activation of LPL by apoC-II can easily be overestimated (30). ITC provided a method to carefully investigate possible effects of apoA-V on the catalytic activity of LPL.…”
Section: Figmentioning
confidence: 99%
“…Preliminary in vitro studies have shown that increasing oleic acid concentrations result in increasing inhibition of both hepatic and lipoprotein lipase activities in a dose-related manner which could be reversed by the addition of excess albumin (I I). The in vitro inhibition of lipoprotein lipase activity by fatty acids has been reported before (1, 2,26) and it has been suggested that fatty acids may have an important physiological role in the feedback control of lipase activity in vivo. It is unlikely that the increased serum triglyceride concentrations in GSD were inhibitory as postheparin plasma from the patient with type 1 hyperlipoproteinemia did not inhibit normal postherapin plasma activity.…”
Section: Discussionmentioning
confidence: 99%
“…For measurement of the activation ability of peptide 39 -62 compared with that of peptide 50 -79, three substrates with different properties were used to explore the activation ability of the apoCII fragments. One was the same as that described above for the mutants, whereas the second one was a gum-arabic-stabilized emulsion of 3 H-labeled trioleoylglycerol prepared as described (15). The conditions were otherwise the same for both systems.…”
Section: Methodsmentioning
confidence: 99%
“…This is the case also for LPL. With substrate emulsions that are less accessible to LPL alone, the activity is more dependent on apoCII, and the -fold activation is, therefore, larger than with simper substrates (15).…”
mentioning
confidence: 99%